Answer:
C. –2x – 10 = –2(x + 5)
Explanation:
Clearer choices:
2x + 10 = –2(x – 5)
–2(x + 5) = 2x – 10
–2x – 10 = –2(x + 5)
–2(x – 5) = –2x – 10
All choices have either:
–2(x – 5) for A and D
or –2(x + 5) for B and C
Simplify these expressions by expanding with the distributive property. Multiply the outside term "–2" with each term inside the brackets.
–2(x – 5)
= (–2*x) – (–2*5) Multiply each term by the coefficient
= –2x – (–10) Simplify the double negative to a positive
= –2x + 10 Expanded expression
This is not the same answer in A and D. They are not correct.
–2(x + 5)
= (–2*x) + (–2*5) Multiply each term by the coefficient
= –2x + (–10) Adding a negative is the same as subtraction
= –2x – 10 Expanded expression
This is the same answer for option C.
Therefore "C" is the answer.